A simulation-based framework for checkpoint design in large-scale crowd management: Case study of the papal mass in philadelphia. (July 2020) - Aros-Vera, Felipe; Sadeghi, Azadeh; Younes Sinaki, Roohollah; Sormaz, Dusan
Highlights: The paper proposes a simulation-based framework to assess checkpoint configurations. The framework assess the capacity of checkpoints and attendee regulations in crowd management. The paper proposes relevant policy recommendations and insights for planning and managing large crowds. The paper delivers an in depth case study of the Papal Mass in the World Meeting of Families on September 27th, 2015. Abstract: This paper develops a simulation-based framework to assess checkpoint configurations, capacity and attendee regulations in crowd management. The simulation uses the estimated crowd and location layout of the event as inputs, and evaluates the performance of checkpoints in terms of average and maximum wait time, and queue length. Similarly, it estimates the percentage of people that will enter the event when the number of attendees surpasses the capacity of checkpoints. The paper provides relevant policy recommendations and insights for planning and managing large crowds. A case study of the Papal Mass in the World Meeting of Families on September 27th, 2015 illustrates the application of the framework. In this event, a large percentage of attendees waited for hours and could not enter the event. The case study highlights the benefits of having two consecutive security rings for different tasks (e.g., backpack screening and metal detector booths). In the case study, adding a second security ring increases by 22% the number of people who would have been able to enter the event. Results also show the negative impact of allowing attendees to bring backpacks to an event. If that is the case, it is recommended to separate the lines of attendees who carry bags and those who do not carry bags to expedite the process.